Determination of Organochlorine Pesticides in Vegetables by Solid-Phase Extraction Cleanup and Gas Chromatography - Chai, Alvin Lian Kuet; Lau, Seng (Universiti Putra Malaysia Press, 2003)
A simple and rapid cleanup procedure has been developed for simultaneous determination of organochlorine pesticides in vegetables. Residues were extracted with acetone and dichloromethane. Extracts were cleaned up by a mixed-mode solid-phase extraction column, quaternary amine and aminopropyJ. The pesticides were determined by gas chromatography with electron capture detector. The recoveries of 6 pesticides in three crops, namely carrot, cucumber and green mustard, fortified at 0.5 mg/kg were in the range of 68% to 109.3%. The results obtained were comparable to those obtained by silica gel cleanup method.